Investigating the relation between health-related quality of life and sleep quality in the Kurdish elderly of Saqqez - Reza Ghanei Gheshlagh; Mohammad Farajzadeh; Maryam Karami; Reza Ahani; Kourosh Sayehmiri (Tehran University of Medical Sciences, 2016)
Background & Aim:Quality of life refers to satisfaction or dissatisfaction with various important life domains. Sleep disorder is one of the factors which can influence the quality of life. This study has been conducted in order to investigate the relation between quality of life and sleep quality in the Kurdish elderly of Saqqez County. Methods & Materials: This correlational study was conducted in 2016 on 292 elderly people in Saqqez County. Data were gathered using, the SF-36 questionnaire and the Pittsburgh Sleep Quality Index. Data analysis was performed by SPSS version 18 and descriptive statistics tests, Kolmogorov-Smirnov test, Spearman's correlation coefficient and Mann-Whitney U test. The statistical significance level was determined as less than 0.05. Results: The average quality of life score and elderly sleep quality were 48.39± 16 and 11±3.6, respectively. Quality of life had a significant correlation with all domains of sleep quality. The educated elderly had higher life and sleep qualities compared to the illiterate ones. Quality of life in men was higher than that of women, but there was no significant difference between them in case of sleep quality. Conclusion: By enhancing the sleep quality, the quality of life will also be improved. Sleep hygiene education seems to be necessary for improving the quality of life in the elderly.